Inclusive Instruction for Students with Emotional Disturbance: An Investigation of Classroom Practice. (March 2022) - McKenna, John William; Newton, Xiaoxia; Brigham, Frederick; Garwood, Justin
A survey was developed to obtain information on practitioner self-reported knowledge, use, and perceived effectiveness of classroom-based practices for the inclusive instruction of students with emotional disturbance (ED). This study reports descriptive results for a sample of general and special education teachers from the northeastern United States who provided inclusive instruction and/or support to at least one student with ED in a general education classroom in the past year. Mann–Whitney and MANOVA tests were employed to determine differences between teacher populations for individual practices and four clusters of practices identified in an exploratory factor analysis (EFA): Behavioral Supports, Differentiation, Classroom Management, and Instructional Practices. Findings suggest that special educators serve an important role in efforts to provide instruction that focuses on inclusion rather than merely integration. Implications for practice, study limitations, and areas for future research are discussed.